Planeamiento estratégico: Calimod - Carrión Portilla, Verónica Alicia (2023)
This work will be based on the Calimod Group or also called Calimod, dedicated to the manufacture of leather footwear for more than 50 years in Peru under the brand called of the same name. In this research, the situation of the company will be analyzed both externally and internally from the brand's perspective, using various strategic evaluation tools to have a more accurate and information-rich diagnosis. The leather footwear industry currently in Peru is considered competitive, but few of them offer the quality and positioning that Calimod has over the years. However, like any company there are always points to improve and Calimod is no stranger to this. Today, it is in a process of wanting to rejuvenate the brand by expanding its segment with the aim of being more profitable and being within the options of potential consumers in the process of choosing a good quality leather footwear but above all that is aesthetically pleasing. That is why, thanks to this research, it will be possible to analyze in depth what must currently be worked on to reach the objectives and strategies will be proposed to achieve it. It is crucial to be at the forefront of trends in this industry that is considered fashion by many, so the design and innovation factor will be a very important point to be able to restructure the guidelines and processes in the manufacture and sale of leather footwear.